1996
DOI: 10.1021/ma9600567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poly(acrylic acid) Electrosteric Stabilizer on Entry and Exit in Emulsion Polymerization

Abstract: A methodology developed to obtain rate coefficients for entry and exit (desorption) in emulsion polymerizations was applied to systems stabilized electrosterically by a copolymer of acrylic acid and styrene embedded in a styrene seed particle. This was grown as a second-stage procedure, by adding styrene and acrylic acid to a styrene seed and then polymerizing. Rate coefficients for entry (ρ) and exit (k) for subsequent homopolymerization of the resulting latices with styrene were obtained from the time depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 32 publications
9
78
0
Order By: Relevance
“…The systems we studied, however, are different because we used a polystyrene seed latex containing no carboxylic groups. Carboxylated seed latexes were also used by Coen et al 30 to study the influence of pH on the emulsion polymerization of S. Poly(acrylic acid) as stabilizer played a crucial role in the mechanism of the polymerization, which is probably also the case in the work of Shoaf and Poehlein. 9,10 Our systems actually describe the carboxylation process of polystyrene latexes and in this context the limited effect of pH on the polymerization rate is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…The systems we studied, however, are different because we used a polystyrene seed latex containing no carboxylic groups. Carboxylated seed latexes were also used by Coen et al 30 to study the influence of pH on the emulsion polymerization of S. Poly(acrylic acid) as stabilizer played a crucial role in the mechanism of the polymerization, which is probably also the case in the work of Shoaf and Poehlein. 9,10 Our systems actually describe the carboxylation process of polystyrene latexes and in this context the limited effect of pH on the polymerization rate is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…36 The data in Table I, however, differ from those reported for the electrosterically stabilized emulsion polymerization of styrene where the desorption of radicals was depressed. [8][9][10] The decreased desorption of radicals was attributed to the thick emulsifier layer formed by the graft copolymer at the polymer particle surface. This difference between the present data and the literature ones might result from the difference in the solubility, the molecular weight and mobility of the stabilizers used.…”
Section: 37mentioning
confidence: 99%
“…This may not be a case for the high molecular weight copolymer. [8][9][10] The reduction in the polymerization rate with increasing the weight ratio of emulsifier and monomer can arise from the breakdown in the extent of compartmentalization of the free radicals in the latex particles and the increased exit of radicals. The decreased extent of compartmentalization of radicals is accompanied with the shapes of the conversion and polymerization rate curves (Figures 1 and 2) typical for the microemulsion polymerization characterized by the strong radical desorption.…”
Section: 37mentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that flocculation of seeded and overcoated particles, poorly stabilized due to swelling in monomer at the absence of surfactants. Effect of stabilizing effectiveness of styrene and acrylic acid copolymer on proceeding of elemental stages of water dispersed polymerization of styrene is studied [38]. It is shown [38,39] that stabilizer forms highly viscous zones around the particles and it leads to decreasing diffusion rates of monomer and oligomer radicals inside PMP and restriction desorption of radicals from particles surface.…”
Section: Introductionmentioning
confidence: 99%